Desarrollo y análisis del sistema conjunto pcr/dot blot para la detección del virus de la necrosis hipodérmica y hematopoyética infecciosa - Castro Lara, Jonathan (2009)
The present work describes development and analysis of a PCR/dot blot system for the detection of IHHNV. The experimental strategy was performed in three phases: 1) cloning of specific regions of the viral genome for generation of oligonucleotide probes to recognize a region of the IHHNV genome, 2) optimization of the PCR/dot blot protocol as a diagnostic tool, and 3) to test the method for diagnostic of IHHNV in Penaeus vannamei. The analysis of sensibility performed in fragments of purified viral DNA showed levels of dot blot detection (without PCR) of 3pg/μl. The use of PCR/dot blot system increased the sensibility of detection to 0.002ag/μl of target DNA, in comparison; the sensibility of PCR without dot blot was 2ag/μl. This increase in sensibility was evident in the laboratory test of P. vannamei samples. Broodstok population was analyzed using PCR and PCR/dot blot, these analyses showed positive signals for IHHNV in 69.83% and 79.9%, respectively. In a similar fashion, a population of juvenile shrimps showed positive signals for IHHNV in 7.48% using PCR and 13.3% using PCR/dot blot. These results support the use of PCR/dot blot system as an alternative method for the sensitive and specific detection of viral genome, as compared to the traditional PCR method.